Spontaneous haemoperitoneum secondary to a Meckel's diverticulum - Jabar, Mohd Faisal; Shaker, Abdul Rahmat Hikmet; Alif Gul, Yunus Gul (ARSMB-KVBMG, 2004)
Meckel’s diverticulum is a relatively common gastrointestinal entity which occasionally causes complications. Meckel’s diverticulum is classically described to mimic acute appendicitis when inflamed as well as being a cause of unexplained luminal gastrointestinal bleeding. An unusual cause of spontaneous non traumatic haemoperitoneum found during surgery performed for a suspected acute appendicitis in a 22-year old female is described. The patient was found to have a significant haemoperitoneum due to a bleeding serosal vessel of a Meckel’s diverticulum. The diverticulum was routinely excised. It was macroscopically and histologically devoid of inflammation. The bleeding vessel was not found to be abnormal or part of an arteriovenous malformation.